Robust tracking control system for longitudinal manoeuvre of large aircraft - Mohmad Rouyan, Nurhana (2023)
A near-stall condition refers to a critical flight situation in which an aircraft is operating at or near its stall velocity or the minimum speed required to maintain lift. During this condition, the aircraft’s aerodynamic performance is severely compromised, making precise control essential for the safe and reliable execution of manoeuvres, including terrain avoidance, evasive manoeuvres, and safe landings or climbing. In such a situation, maintaining stability and control becomes paramount to ensure the safety of the aircraft and its occupants. As flight control systems continue to incorporate the latest automation technology, it is essential to assess the effectiveness of these systems in such conditions. However, aircraft models inherit nonlinearity due to near-stall conditions. In addition to addressing the lack of effective control solutions in existing systems, this thesis explores the application of sliding mode control (SMC) to maintaining satisfactory flight performance during manoeuvres that require rapid changes in attitude, altitude, and velocity in the tracking process. A nonlinear aircraft model was developed for this purpose, and the model was transformed into a nonlinear state space to provide an accurate representation of the aircraft dynamics. To verify the model, open-loop analysis was employed based on the trimming and linearisation of the model. Additionally, variants of SMC, including integral SMC (ISMC) and non-singular terminal SMC (NTSMC), were integrated into the aircraft model to evaluate their potential for enhancing flight stability and performance. The model underwent various flight phase scenarios to demonstrate the effectiveness of these control methods in challenging situations. The results were compared with PID and SMC controllers as baselines. The study revealed that the sliding surface variable is critical for determining the stability performance of the aircraft, with the tested controllers outperforming the baselines. Notably, NTSMC exhibited nearly a 60% improvement in response compared to PID. However, achieving simultaneous control for attitudes and velocity has posed challenges, emphasizi-ing the necessity of a hierarchical control structure.